ANALYSIS OF ILLOCUTIONARY ACTS IN DONALD TRUMP’S STATE OF THE UNION ADDRESS - Hannytiananda, I Gusti Agung; Soethama, Putu Lirishati (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The analysis discusses the illocutionary acts and forces in Donald Trump’s 4th of February, 2024 State of the Union address. Based on the analysis that has been conducted, it aimed to interpret and describe the illocutionary acts and forces in Donald Trump’s State of the Union address. A qualitative method was used toanalyze this research. The research also applied Searle and Bach and Harnish’s theory. Searle’s theory is used to interpret the illocutionary acts, whereas Bach and Harnish’s theory was used as an indicator of the illocutionary forces. The results of the analysis found all five of the classifications of illocutionary act, which consisted of a total of twenty-two samples, namely, assertives, directives, commissives, expressives, and declarations. In the analysis results, assertives were predominantly found in Donald Trump’s State of the Union address with the total of 266 data, which dominantly described how important the act of assertive is in political discourse as it is used as a way to persuade the hearer. The remaining acts that were found are directives with the total of twenty-eight data, commissives with the total of fourteen data, expressives with the total of twenty-two data, and declrations with the total of two data. The statements of Donald Trump that were analyzed did not include all of the classifications of illocutionary forces by Bach and Harnish, with assert as the dominant force in assertive act, requesting in the directive act, promising in commissive act, and thanking in expressive act. The act of declaration does not have illocutionary force.